LAW ENFORCEMENT IN CRIMINAL OFFENCES IN THE 2020 REGIONAL HEAD ELECTIONS (PILKADA) IN BINJAI CITY BY INTEGRATED LAW ENFORCEMENT CENTER (Study on the General Election Supervisory Body of Binjai City) - Khairunnisa; Mirza Nasution; Abdul Aziz Alsa (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
The Unitary State of the Republic of Indonesia is a constitutional state that places the highest sovereignty in the hands of the people, as referred to in Article 1 paragraph (2) of the 1945 Constitution of the Republic of Indonesia, which reads: "Sovereignty is in the hands of the people and is implemented according to the Constitution". Based on the statement above, making Indonesia a democratic country, so that not only leaders but also all Indonesian people have full rights to determine the principles of good governance. Basically, a democratic system is a form of government where all citizens have the same rights in determining decisions that can change their lives. The democratic system allows citizens to participate, both directly and through representatives in the formulation, development and creation of laws. The research was conducted in Binjai City, precisely at the Binjai City Bawaslu Gakkumdu Center. This research uses an empirical legal approach method, data obtained in the field are presented descriptively using an empirical normative approach method. This study aims to determine the form of criminal acts in the 2020 regional head election (pilkada) in Binjai City, Law enforcement of criminal acts in the 2020 regional head election (pilkada) in Binjai City, and the role of the Integrated Law Enforcement Center (Sentra Gakkumdu) in handling criminal acts in the 2020 regional head election (pilkada) in Binjai City. Based on the results of the research that the author obtained, in the data on handling violations of the 2020 Regional Head Election in Binjai City, there were 5 (five) handling of alleged election crime violations, consisting of 2 (two) Findings based on the results of supervision by the Binjai City General Election Supervisory Agency and 3 (three) Reports from the public, In enforcing the law on election crimes, especially in Binjai City in the 2020 Binjai Mayor and Deputy Mayor Election, the principle of fast law enforcement is used, meaning that in terms of law enforcement on election crimes, it is carried out quickly and there is a time limit that is relatively faster than handling crimes in general, where the General Election Supervisory Agency together with police investigators and prosecutors will conduct the first discussion within a maximum of 1 x 24 hours from the date the findings or reports are received and registered by the General Election Supervisory Agency, That the Integrated Law Enforcement Center (Sentra Gakkumdu) has the main function and role in conducting case titles to identify elements of election crimes and evidence that must be collected, then the work procedures in handling election crimes which include receiving reports, first discussion, second discussion, investigation, third discussion, and prosecution with the aim of achieving a common understanding in handling election crime cases.